Replik til Kaare Rübner Jørgensen - Rasmussen, Jørgen Nybo (Kirkehistoriske Samlinger, 2011)
Summary Kaare Rübner Jørgensen’s (KRJ) intention is to prove that the results of my research on the life and identity of the Franciscan friar Jakob the Dane (c. 1483-1566) are fundamentally erroneous. KRJ claims that my sources are unreliable, and he dismisses my use of them. In answer to this, I first present a brief survey of the historical picture of Friar Jakob through the centuries, concluding with my own lifelong studies. Then I show how KRJ’s own paradigms have led him to this excessive criticism. According to himself, his judgments are mainly influenced by two specific theories of interpretation: »deconstructivism« and »demythologization«. Directed by these guidelines, he cast doubts on the reliability of the most important sources. This is, however, an arbitrary and unacceptable use of foreign theories taken from other disciplines such as literary history and theology, and they are not suitable for evaluation of historical sources. Therefore KRJ’s rejection of my work must essentially be dismissed as a mistake. I exemplify this by dealing with one important question, namely whether Friar Jakob really was born a member of the Danish Royal House? From the 16.th. century onwards, all Mexican, Spanish and Franciscan texts say that he was. My studies have consisted in a thorough investigation of these and all other available sources about him in the Old and the New World. KRJ dismisses the Mexican primary sources as »mythological« and therefore unreliable. He rejects their information about Jakob’s royal birth as Franciscan wishful thinking based on Jakob’s surname in Mecklenburg, »Gottorpius«, because »Gottorp was a castle«! But the only surname Jakob actually used in Mexico was »Dane« or »Danish«. He alone could have told his superiors about his identity. KRJ’s claim is unfair, and even curious, because elsewhere he rejects my interpretation of »Gottorpius«. Jakob only used this name in 1539 in Mecklenburg during the dynastic conflict in Denmark, but at the same time he confirmed his Franciscan vocation by calling himself »Provincial Minister of Dacia«. In this way he manifested his origin as the younger brother of the emprisoned king Christian II, analogous to the first division of the Duchies in 1490. In contrast to other historians, KRJ denies that »Gottorpius« may have had this meaning at that time. But the decisive witness for Jakob’s affiliation with the Danish royal family is the historian of the county of Oldenburg, Hermann Hamelmann. His list of the three eldest sons of King Hans and Queen Christine names them: »Johan, Carsten (Christian) and Jakob«. KRJ’s objection is that Christian II was later called »primogenitus«, whereas Hamelmann placed him as the second son. The explanation is that Johan died prematurely, and when Christian later was recognized as heir to the throne, the documents never referred to him as »first-born«, but only as »son« or »elder son« of King Hans. Only Paulus Heliæ used the term »primogenitus« about him c. 1520. These examples suffice to show how I have answered the criticisms of KRJ. His objections are insufficient as demonstrations of the alleged shortcomings of my research of the life of Friar Jakob the Dane.